The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0033294116687298
|View full text |Cite
|
Sign up to set email alerts
|

Is Trypophobia a Phobia?

Abstract: In the past 10 years, thousands of people have claimed to be affected by trypophobia, which is the fear of objects with small holes. Recent research suggests that people do not fear the holes; rather, images of clustered holes, which share basic visual characteristics with venomous organisms, lead to nonconscious fear. In the present study, both self-reported measures and the Preschool Single Category Implicit Association Test were adapted for use with preschoolers to investigate whether discomfort related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…It has been suggested that a trypophobic reaction may be an extension of an intrinsic disgust for decomposing items, sores and scars, which would aid in the avoidance of contaminated stimuli specifically and disease more generally ( Cole & Wilkins, 2013 ; Deacon & Olatunji, 2007 ; Rozin & Fallon, 1987 ; Skaggs, 2014 ). Holes, but not spiders and snakes, or other repetitive patterns, may have come to be associated with disease transmission ( Rozin & Fallon, 1987 ), either over the course of evolution or learned during ontogenetic development ( Can, Zhuoran & Zheng, 2017 ; Kupfer & Le, 2017 ). The result of this association may be a corresponding withdrawal response controlled by the parasympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a trypophobic reaction may be an extension of an intrinsic disgust for decomposing items, sores and scars, which would aid in the avoidance of contaminated stimuli specifically and disease more generally ( Cole & Wilkins, 2013 ; Deacon & Olatunji, 2007 ; Rozin & Fallon, 1987 ; Skaggs, 2014 ). Holes, but not spiders and snakes, or other repetitive patterns, may have come to be associated with disease transmission ( Rozin & Fallon, 1987 ), either over the course of evolution or learned during ontogenetic development ( Can, Zhuoran & Zheng, 2017 ; Kupfer & Le, 2017 ). The result of this association may be a corresponding withdrawal response controlled by the parasympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that the spectrum of the trypophobic images is similar to that of poisonous animals and speculated that this visual property induces an avoidance reaction (Cole & Wilkins, 2013). However, a subsequent study showed that trypophobic objects were not associated with poisonous animals (Can, Zhuoran, & Zheng, 2017). On the other hand, Yamada and Sasaki (2017) recently proposed a new possible explanation: The "involuntary protection against dermatosis" (IPAD)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Can et al ( 19 ) questioned whether trypophobia is really a phobia, given that previous reports showed people commonly feel disgust rather than fear when confronted to trypophobic images. Hence, if trypophobia does not involve fear in most cases, it might not be a specific phobia.…”
Section: Discussionmentioning
confidence: 99%